1992
DOI: 10.1039/ja9920700081
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of individual environmental particles. Plenary lecture

Abstract: Applications of instrumental microanalysis techniques for the characterization of individual particles in environmental samples are reviewed. The principles of electron microprobe analysis and related techniques, the micro-version of proton-induced X-ray emission, laser microprobe mass spectrometry, secondary ion mass spectrometry and Raman microprobe analysis, are briefly reviewed and their published applications to aerosols and to aqueous suspensions are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…21 -25 However, in previous studies direct evidence for the counter-anion, i.e. carbonate itself, was generally absent, other than a low-abundance radical species in the anion spectrum that corresponded to CO 3 .…”
Section: Introductionmentioning
confidence: 77%
“…21 -25 However, in previous studies direct evidence for the counter-anion, i.e. carbonate itself, was generally absent, other than a low-abundance radical species in the anion spectrum that corresponded to CO 3 .…”
Section: Introductionmentioning
confidence: 77%
“…Earlier reviews have pointed out that EPXMA, laser microprobe mass analysis (LMMS) and micro-particle induced X-ray emission (µ-PIXE) are the techniques most used for environmental applications [1][2][3][4]. Other techniques like scanning transmission electron microscopyenergy dispersive X-ray detection (STEM-EDX), electron energy loss spectrometry (EELS), micro-Raman spectrometry, Fourier transform infra red microscopy (µ-FTIR) and secondary ion mass spectrometry (SIMS) have only found limited applications in environmental research or have only been recently discovered by environmental laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…This article will give an overview of the micro-analytical applications on single particles performed in the Micro-and Trace Analysis Centre (MiTAC) of the University of Antwerp since 1990. For descriptions of the microanalytical techniques involved and for other environmental applications, reference is made to Grasserbauer [1], Van Grieken and Xhoffer [2], Xhoffer et al [3] and Jambers et al [4]. and characterise the composition of "pure" aerosols in the absence of any pollution.…”
Section: Introductionmentioning
confidence: 99%
“…33,34,35,36,37,38 Those species which are most responsible for toxic manifestation exist on the top-most layer of environmental surfaces, because they are most susceptible to solubilization, and consequent mobility and uptake. For this reason, a goal is to understand metal speciation at mineral surfaces.…”
Section: Overview: Chemical Investigations and Instrument Developmentmentioning
confidence: 99%
“…The utilization of a cytochrome compound that is present in the cell membrane would be a logical explanation based upon a normal respiratory chain. Indeed, iron reduction has been shown to occur on or near the surfaces of cells of other microorganisms including Listeria spp, 32 Neisseria gonorrhoeae, 33 Saccharomyces cerevisiae, 34,35 and Vibrio (Listonella) anguillarum 28 using enzymes most frequently identified as cytochromes. Cytochromes have also been identified that may play a role in the reductive dechlorination activity on or near the surface of certain other types of bacteria.…”
mentioning
confidence: 99%